Gone in 60 days: our first experience with a bioconvertible IVC filter - O'Mahony, Johnny; Donohoe, Claire; Ryan, J (Springer Science and Business Media LLC, 2021)
The Sentry bioconvertible IVC filter (Boston Scientific, MA, USA) contains a bioabsorbable filament which hydrolyses after 60 days, allowing the arms of the filter to spring open, retract into the vessel wall and endothelialise, leaving an unobstructed IVC lumen. It is a novel treatment option for patients at transient risk of pulmonary emboli with a contraindication to anticoagulation. The device provides similar protection to other currently available devices against pulmonary emboli with minimal complications. It represents an effective alternative to retrievable filters, the removal of which is variously not attempted, not possible or associated with high complication rates. We review the literature which underpins the development of the bioconvertible filter. We describe our first deployment of the filter in an 85-year-old female with gastric malignancy (who subsequently underwent a subtotal gastrectomy) with a history of anaemia and previous pulmonary emboli. The availability of a bioconvertible filter constitutes a further step forward in the management of patients with potential or active thromboembolic disease.
PUBLISHED
Keywords: IVC filter; Bioconversion; Deep venous thrombosis; Pulmonary embolism; Retrieval; Anticoagulation